The Role of Surgery in the Management of Acute Pancreatitis - Beat Gloor; Waldemar Uhl; Christophe A Müller; Markus W Büchler (Canadian Journal of Gastroenterology)
The clinical course of an episode of acute pancreatitis varies from a mild, transitory form to a severe necrotizing form characterized by multisystem organ failure and mortality in 20% to 40% of cases. Mild pancreatitis does not need specialized treatment, and surgery is necessary only to treat underlying mechanical factors such as gallstones or tumours at the papilla of Vater. On the other hand, patients with severe necrotizing pancreatitis need to be identified as early as possible after the onset of symptoms to start intensive care treatment. In this subgroup of patients, approximately 15% to 20% of all patients with acute pancreatitis, stratification according to infection status is crucial. Patients with infected necrosis must undergo surgical intervention, which consists of an organpreserving necrosectomy followed by postoperative lavage and/or drainage to evacuate necrotic debris, which appears during the further course of the condition. Primary intensive care treatment, including antibiotic treatment, delays the need for surgery in most patients until the third or fourth week after the onset of symptoms. At that time, necrosectomy is technically easier to perform and the bleeding risk is reduced, compared with necrosectomy earlier in the disease course. In patients with sterile necrosis, the available data strongly support a conservative approach (ie, intensive care unit treatment). Surgery is rarely necessary in these patients.